Bone Tuberculosis: Rare Condition Among Infants - Bastola, Ramchandra; Adhikari, Neelam; Shrestha, Dhruba; Sigdel, Bhawana; Shrestha, Shree Krishna (Journal of Nepal Paediatric Society, 2019)
Bone tuberculosis in infancy has become rare these days. Here we report a case of 12 months old male infant who had presented with complaints of fever and skin rash for one month, along with protuberance of toe joint for 15 days. He was being treated with antibiotics, vitamin D and calcium without improvement. Further investigations led to mycobacterium positivity in bone biopsy. He was treated with anti-tubercular therapy and he responded to the treatment dramatically. So, though rare, it is important to consider bone tuberculosis when there are bony issues even in infancy, especially in endemic regions like ours.